Decadence, radicalism, and the early modern French nobility the enlightened and depraved - Denton, Chad 1981- (Lexington Books, 2017)
Introduction: a libertine nobility -- Refinement and the court nobility -- A libertine nobility -- The liberated sodomite -- Institutionalizing adultery -- Marie Antoinette, the Revolution, and the end of the libertine nobility -- Conclusion